Effect of statins on creatine kinase levels before and after a marathon run - Parker, B. A.; Augeri, A. L.; Capizzi, J. A.; Ballard, K. D.; Troyanos, C.; Baggish, A. L.; D'Hemecourt, P. A.; Thompson, P. D. (The American Journal of Cardiology, 2012)
We measured the serum levels of myoglobin, total creatine kinase (CK), and the CK myocardial (CK-MB), muscle (CK-MM), and brain (CK-BB) isoenzymes in 37 subjects treated with statins and 43 nonstatin-treated controls running the 2011 Boston Marathon. Venous blood samples were obtained the day before (PRE) and within 1 hour (FINISH) and 24 hours after (POST) the race. The hematocrit and hemoglobin values were used to adjust for changes in the plasma volume. The CK distribution was normalized using log transformation before analysis. The exercise-related increase in CK 24 hours after exercise, adjusted for changes in plasma volume, was greater in the statin users (PRE to POST 133 ± 15 to 1,104 ± 150 U/L) than in the controls (PRE to POST 125 ± 12 to 813 ± 137 U/L; p = 0.03 for comparison). The increase in CK-MB 24 hours after exercise was also greater in the statin users (PRE to POST 1.1 ± 3.9 to 8.9 ± 7.0 U/L) than in the controls (PRE to POST 0.0 ± 0.0 to 4.2 ± 5.0 U/L; p <0.05 for comparison). However, the increases in muscle myoglobin did not differ at any point between the 2 groups. Increases in CK at both FINISH and POST race measurements were directly related to age in the statin users (r2 = 0.13 and r2 = 0.14, respectively; p <0.05) but not in the controls (r2 = 0.02 and r2 = 0.00, respectively; p >0.42), suggesting that susceptibility to exercise-induced muscle injury with statins increases with age. In conclusion, our results show that statins increase exercise-related muscle injury.